Review of Company Compliance with Occupational Safety and Health Standards - Utomo, Bekti (International Journal of Integrative Sciences, 2025)
This study used the field inspection method, which involves a direct visit to a work site to observe and evaluate the implementation of occupational safety (OSH) standards. Data were collected through direct observation, interviews with relevant personnel, and examination of OHS-related documents. A sample of companies was randomly selected from various industrial sectors to represent a wider range of people.The objectives of this study are many-fold. As a first step, the study aimed to evaluate the company's utomo of compliance with applicable OHS standards. It is important to know the general level of compliance in the workplace. In addition, the purpose of the study was to find places where compliance may not be fully met. This identification can form the basis for improvement initiatives.Research Background The importance of occupational safety and health (OHS) standards to safeguard employee welfare and company performance, research on the review of companies' compliance with OHS through a field inspection approach is highly relevant. This background is due to the fact that OHS standards have been established and regulated, but companies' compliance with these standards is often inconsistent.According to the study, there are differences in the level of companies' compliance with OHS standards. While some companies have low levels of compliance, others still have low levels of compliance. Compliance is often breached in areas such as the use of personal protective equipment, emergency evacuation procedures, andhandling of hazardous chemicals. Lack of OHS training, lack ofmanagement oversight, and high production priorities are some of the factors affecting compliance.In conclusion, this study emphasizes how important it is to improve OHS standards in companies to make the working environment safer and healthier. Suggested improvements include more OHS training, more management supervision, and more sanctions for OHS violations